2009
DOI: 10.4049/jimmunol.0900043
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Protects Mice from Lethal Endotoxic Shock via a Rapid Induction of MAPK Phosphatase-1

Abstract: The nonessential amino acid l-glutamine (Gln) is the most abundant amino acid in plasma. Clinical trials have demonstrated that Gln therapy is safe and improves clinical outcomes in critically ill patients. We have previously shown that Gln protect animals from endotoxic shock through the inhibition of cytosolic phospholipase A2 activity. In this study, we investigated how Gln regulates MAPK activation, as the molecular mechanism underlying Gln-induced cytosolic phospholipase A2 inactivation. Gln rapidly (with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 48 publications
9
50
0
Order By: Relevance
“…It was found that propofol could effectively inhibit inflammation caused by endotoxin. Serum levels of inflammatory factors such as IL-6 and TNF-a were significantly decreased upon propofol treatment (Ko et al, 2009;Hammer et al, 2010). Further cell experiments also suggested that propofol could stabilize the cell membrane and reduce inflammatory factors secreted by macrophages and T cells released in the inflammation.…”
Section: Discussionmentioning
confidence: 82%
“…It was found that propofol could effectively inhibit inflammation caused by endotoxin. Serum levels of inflammatory factors such as IL-6 and TNF-a were significantly decreased upon propofol treatment (Ko et al, 2009;Hammer et al, 2010). Further cell experiments also suggested that propofol could stabilize the cell membrane and reduce inflammatory factors secreted by macrophages and T cells released in the inflammation.…”
Section: Discussionmentioning
confidence: 82%
“…Clinical trials in human subjects have also demonstrated that Gln treatment decreases infectious complications, shortens hospital stay, and decreases hospital costs in a number of patient populations (18). Regarding the mechanisms, we have shown that Gln inhibits cytosolic phospholipase A 2 (cPLA 2 ) activity (19) by deactivating p38 and JNK MAPKs (20). As a result, Gln exhibits a beneficial effect on murine asthma (21).…”
mentioning
confidence: 92%
“…Gln was dissolved in sterilized distilled water to 3%. A volume of 0Á5 ml (750 mg/ kg) [12][13][14][15] was administered intraperitoneally (i.p.) 10 min before or 10 min after LPS injection.…”
Section: Reagentsmentioning
confidence: 99%
“…Isolated lung tissues were frozen in liquid nitrogen and stored at 270 C until analysis. Small lung specimens were homogenized in PhosphoSafe Extraction Reagent (Novagen, Madison, WI, USA) and subjected to immunoblotting analysis, as described previously [15].…”
Section: Immunoblotting Analysismentioning
confidence: 99%
See 1 more Smart Citation